Coal characteristics and biomarker investigations of Dombayova coals of Late Miocene–Pliocene age (Afyonkarahisar-Turkey). (April 2016) - Bechtel, Achim; Karayigit, Ali Ihsan; Bulut, Yilmaz; Mastalerz, Maria; Sachsenhofer, Reinhard F.
Highlights: Coal characterization of newly-discovered Dombayova deposit. Lignite-formation occurred in low-lying mire under alkaline pH. Differences in functional group abundances in lignite macerals are evidenced by micro-FTIR. Reducing conditions during coal formation in the lower seams argue for higher groundwater level. Terpenoid biomarkers indicate a major contribution of angiosperms. Abstract: In Dombayova graben (Dinar-Afyonkarahisar, western Turkey) a 203-m-thick coal-bearing zone of Late Miocene to Pliocene age was recently drilled. The zone hosts several coal beds with a total thickness of 46 m. Coal samples from the Dombayova field were studied by means of standard proximate, ultimate, petrological analyses, micro-FTIR spectroscopy and Rock-Eval pyrolysis, and organic geochemical analyses. Coal proximate analyses and the presence of carbonate minerals and fossil shell fragments point to alkaline surface waters of changing pH-values due to fluctuations of the water level in the paleomire and/or Ca-rich water influx. Low sulfur contents argue for sulfate-limitation of bacterial sulfate reduction. Petrographic observations reveal that the coal is dominantly composed of weakly altered wood fragments and roots. The mean random reflectance values of ulminite (0.33 %Ro) indicate lignite rank of the coal. The micro-FTIR data of macerals of huminite group indicate higher contributions of aliphatic hydrogen in textinite, compared to more aromatic levigelinite. The semi-quantitative differences in the ratios of selected functional groups suggest that aromaticity and the extent of oxidation are higher in levigelinite. Aliphatic chains are longest in textinite and ulminite, and shortest in texto-ulminite and levigelinite. We interpret this difference to point to a different origin of levigelinite, probably from colloidal humic solutions that were gelified during diagenesis. The concentrations of n -alkanes and their distribution patterns provide evidence for higher terrestrial plants as the dominant source of organic matter. Decreasing pristane/phytane ratios with depth are interpreted to reflect more reducing conditions during peat formation due to higher (ground)water level. The absence of diasterenes is most probably caused by low clay mineral contents and is consistent with the presence of alkaline waters in the paleomire. The presence of terpenoid hydrocarbons in the lignite indicates a major contribution of angiosperms to peat formation. The positive relationship between the concentrations of perylene and lupane-type triterpenoids suggests an increasing abundances of wood-degrading fungi in the peat-forming vegetation characterized by a high density of Betulaceae.